Battle for Malaya : The Indian Army in Defeat, 1941-1942 - Roy, Kaushik, 1971- (Book collections on Project MUSE., 2019)
"The defeat of 90,000 Commonwealth soldiers by 50,000 Japanese soldiers made the Battle for Malaya during World War II an important encounter for both political and military reasons. British military prestige was shattered, fanning the fires of nationalism in Asia, especially in India. Japan's successful tactics in Malaya-rapid marches, wide outflanking movement along difficult terrain, nocturnal attacks, and roadblocks-would be repeated in Burma in 1942-43. Until the Allied command evolved adequate countermeasures, Japanese soldiers remained supreme in the field. Focusing on tactics of the ground battle that unfolded in Malaya between December 1941 and February 1942, rather than the failures of command, Kaushik Roy analyzes the organization of the imperial armies, looking primarily at the Indian Army, which comprised the largest portion of Commonwealth troops, and compares that army with those of Britain and Australia, which fought side by side with Indian soldiers. Utilizing both official war office records and unofficial memoirs, autobiographies, and oral histories, Roy presents a synthesis of history from the top with history from below and provides a thick narrative of operations interwoven with tactical analysis of the Battle for Malaya from both sides"--